Dynamic Regulation of Histone Modifications in Xenopus Oocytes through Histone Exchange - Stewart, M. David (American Society for Microbiology, 2006)
Histone H3 lysine 9 (H3K9) methylation has broad roles in transcriptional repression, gene silencing, maintenance of heterochromatin, and epigenetic inheritance of heterochromatin. Using Xenopus laevis oocytes, we have previously shown that targeting G9a, an H3K9 histone methyltransferase, to chromatin increases H3K9 methylation and consequently represses transcription. Here we report that treatment with trichostatin A induces histone acetylation and is sufficient to activate transcription repressed by G9a, and this activation is accompanied by a reduction in dimethyl H3K9 (H3K9me2). We tested the possibility that the reduction in H3K9me2 was due to the replacement of methylated H3 with unmethylated H3.3. Surprisingly, we found that both free H3 and H3.3 are continually exchanged with chromatin-associated histones. This dynamic exchange of chromatin-associated H3 with free H3/H3.3 was not affected by alterations in transcriptional activity, elongation, acetylation, H3K9 methylation, or DNA replication. In support of this continual histone exchange model, we show that maintenance of H3K9 methylation at a specific site requires the continual presence of an H3K9 histone methyltransferase. Upon dissociation of the methyltransferase, H3K9 methylation decreases. Taken together, our data suggest that chromatin-associated and non-chromatin-associated histones are continually exchanged in the Xenopus oocyte, creating a highly dynamic chromatin environment.